Clinical and cost outcomes from different hyaluronic acid treatments in patients with knee osteoarthritis: evidence from a US health plan claims database - Vinod Dasa; Mitch DeKoven; Kainan Sun; Allan Scott; Sooyeol Lim (BioExcel Publishing Ltd, 2016)
Background: Intra-articular injection of hyaluronic acid (HA) for knee osteoarthritis (OA) effectively reduces pain and delays total knee replacement (TKR) surgery; however, little is known about relative differences in clinical and cost outcomes among different HA products. Objective: To compare disease-specific costs and risk of TKR among patients receiving different HA treatments in a commercially insured cohort of patients with knee OA in the USA. Method: Retrospective analyses using IMS Health's PharMetrics Plus Health Plan Claims Database were conducted by identifying knee OA patients with claims indicating initiation of HA treatment at an 'index date' during the selection period (2007-2010). Patients were required to be continuously enrolled in the database for 12 months preindex to 36 months postindex. A generalized linear model (GLM) with a gamma distribution and log-link function was used to model aggregate patient-based changes in disease-specific costs. A Cox proportional hazards model (PHM) was used to model the risk of TKR. Both multivariate models included covariates such as age, gender, comorbidities, and preindex healthcare costs. Results: 50,389 patients with HA treatment for knee OA were identified. 18,217 (36.2%) patients were treated with HA products indicated for five injections per treatment course (Supartz and Hyalgan). The remainder were treated with HA products indicated for fewer than five injections per treatment course, with 20,518 patients (40.7%) receiving Synvisc; 6,263 (12.4%), Euflexxa; and 5,391 (10.7%), Orthovisc. Synvisc- and Orthovisc-injected patients had greater disease-specific costs compared to Supartz/Hyalgan (9.0%, p<0.0001 and 6.8%, p=0.0050, respectively). Hazard ratios (HRs) showed a significantly higher risk of TKR for patients receiving Synvisc compared to Supartz/Hyalgan (HR=1.069, p=0.0009). Patients treated with Supartz/Hyalgan, Euflexxa, and Orthovisc had longer delays to TKR than those treated with Synvisc. Conclusion: Analysis of administrative claims data provides real-world evidence that meaningful differences exist among some HA products in disease-specific cost and time to knee replacement surgery.